Lab-on-a-disc for simultaneous determination of total phenolic contents and antioxidatn activity in beverage samples - Y. Kim (2018)
© 15CBMS-0001. We present a fully automated lab-on-a-disc designed for the rapid determination of total phenolic contents (TPC) and antioxidant activity (AA) in beverage samples. Taking advantages of lab-on-a-disc in simple operation, automation, we integrated two methods; Folin-Ciocalteu (FC) method and ferric reducing antioxidant power (FRAP) method for determining TPC and AA, respectively. Compared to a conventional manual TPC and AA detection methods, our platform show reduced analysis time by 9 times for FC and 3 times for FRAP. Our device successfully detected and compared the TPC and AA from 8 different beverage samples including various fruit juice, tea, wine, and beer.